Assessment of the Burden on Caregivers of Patients with Mental Disorders- A cross-sectional study - Acharya, Pratiksha; Upadhyay, Hari Prasad; Loganathan, N. (Journal of Karnali Academy of Health Sciences, 2019)
Background: Mental illness is the condition that disrupts a person’s thinking, feeling, mood, ability to relate to others and daily functioning. Caregivers play an important role in the management of all the chronic mental illnesses. Thus the aim of this study was to assess the burden and to find out association between level of burden among caregivers of mentally ill patients and related variables.Material and Method: An analytical cross-sectional, study was conducted among the caregivers of mentally ill patients visiting at selected Hospital of Bharatpur. Burden Assessment Scheduled (BAS) tool was used to collect the data. Chi-square test was used to find the association between levels of burden with related variables. P-value less than 0.05 were considered as statistically significant.Results: Research showed that among 204 caregivers 61.8% had moderate level of burden and none of the caregivers had mild level of burden however 38.2% had severe level of burden. The statistically significant factors that affect the level of burden in the caregivers are: place of residence, relation with the patient, duration of mental illness, duration of care giving and monthly expenditure for treatment are the statistically significant variables to the level of burden.Conclusion: More than one third of the caregivers have severe level of burden. The level of burden is high among the female as among the male. Caregivers who are married and education status less than primary level have high level of burden. Also, the caregivers who are from nuclear family and whose patient’s duration of mental illness more than one year had severe level of burden.  The statistically significant factors that affect to the level of burden are: place of residence, relation with the patients, and duration of mental illness, duration of care giving and monthly expenditure for treatment.